GeSeTe-based OTS selector integrated with ReRAM for high-density 1S-1R memory arrays - Hyun Kyu Seo; June Hyuk Lee; Min Kyu Yang (AIP Advances)
In this study, we developed a high-performance binary Ovonic Threshold Switching (OTS) selector based on GeSeTe and a resistive random access memory (ReRAM) device based on TaOx. These were integrated into a 1 Selector-1 ReRAM (1S-1R) architecture to address challenges in high-density memory and advanced computing. The GeSeTe-based OTS selector exhibited a high switching ratio (Ion/Ioff > 105), ultra-low off-current (∼1 nA), and fast switching speed (<10 ns), while the TaOx-based ReRAM achieved a high on/off ratio (>20), rapid switching (100 ns), excellent endurance (>109 cycles), and stable retention at 125 °C. The integrated 1S-1R structure effectively suppressed leakage currents using a 1/2 bias scheme and was scaled to a 1 kb X-point memory array. The array demonstrated stable conductance distribution and efficient multiply-and-accumulate operations, with consistency between experimental and theoretical results validating its scalability and reliability. This work highlights the potential of the 1S-1R architecture for next-generation memory and neuromorphic systems, providing a scalable, energy-efficient solution for data-intensive applications by leveraging the complementary strengths of GeSeTe-based OTS selectors and TaOx-based ReRAM devices.